Macro- and microscopic analyses of piles formed by Platonic solids. (21st September 2019) - Zhao, Haiyang; An, Xizhong; Dong, Kejun; Yang, Runyu; Xu, Fan; Fu, Haitao; Zhang, Hao; Yang, Xiaohong
Highlights: The repose angle of piles does not decrease with the particle sphericity. The shear stress dips are more profound than the pressure dips. Characterizations of structures and forces well explain bottom pressure/stress dip. Friction has large influence on Platonic piles. Abstract: Sandpiles are ubiquitous in nature and engineering applications but still not fully understood due to the complexity of structures and materials properties. This work presents a systematic study on the piles of Platonic solids using the discrete element method (DEM), mainly focusing on the effect of particle shape on the repose angles and bottom pressure distributions of the piles. Five Platonic particles (tetrahedron, cube, octahedron, dodecahedron, and icosahedron) were discharged to form wedge-shaped piles. It was found that the repose angle did not increase with the decrease of particle sphericity. The pile formed by the cubes had the maximum repose angle and its bottom stress dip phenomena were more significant in terms of dip width and depth than that of other particle piles. The pressure distributions at different heights of the piles were quite similar to those of the whole piles, while the shear stress distributions near the boundaries exhibited different characteristics for the cube piles. The analyses of packing structures in terms of coordination number, radial distribution function, as well as contact types inside the piles were discussed to understand the change of pressure dips. The influence of static friction on the repose angle was more significant and it enhanced the stress dip phenomenon.